Review of foreign literature on the problem of children and adolescent obesity and its sequelae - L.M. Bulat; O.V. Lysunets; N.V. Didyk (Zaslavsky O.Yu., 2022)
The purpose is to study modern prevalence of overweight in the children's population, sequelae of this physical disorder and to analyze new diagnostic biomarkers comorbidity in obesity. The data of professional domestic and foreign literature were processed and generalized. Diagnostic criteria of overweight in childhood introduced by the European, American professional societies and the World Health Organization guidelines have some features and are not identical and unified. Body mass index and percentage of fat tissue are common important clinical criteria. The main pathogenetic links that are activated in overweight children and lead to the long-term consequences are the inflammatory response, mitochondrial and endothelial dysfunction, which is associated with the manifestation of pulmonary comorbidity and impaired cardiovascular well-being. The mortality rate associated with acute coronary syndrome is likely to be higher in patients with very high body mass index than in those with lower weight (7.1 vs. 4.8 ‰). Endothelial dysfunction at the preclinical level of damage to organs and systems determines the severity of the disease in the future, being the cause of comorbidity. Intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 determine the degree of activity of circulating endothelial cells (CEC). There is a positive correlation between CEC activity, increased visceral adipose tissue, and low-density lipoprotein cholesterol, while the amount of CEC is associated with adipose tissue volume and the level of systolic blood pressure. Qualitative and quantitative changes in CEC can be used as diagnostic markers when forming risk groups for further monitoring and control.